Movie Language Orientation, Gender, Movie Smoking Exposure, and Smoking Susceptibility among Youth in Mexico. Issue 11 (24th July 2017) - Lorenzo-Blanco, Elma I; Abad-Vivero, Erika N; Barrientos-Gutierrez, Inti; Arillo-Santillán, Edna; Pérez Hérnandez, Rosaura; Unger, Jennifer B; Thrasher, James F
Abstract: Introduction: As a result of globalization, youth in Mexico may be exposed to US culture remotely. This remote intercultural contact may influence their movie language orientation and cigarette smoking. To examine how intercultural contact with U.S. culture influences the smoking behaviors of youth in Mexico, this study investigated the influence of English- and Spanish-language movie orientation on movie smoking exposure through US- and Mexico-produced movies. It also examined whether youth movie smoking exposure was associated with higher positive smoking-related expectancies and greater intentions to smoke cigarettes. Methods: Participants were 7524 adolescent never smokers in Mexico (51% female, M age = 12.39 years) who completed a school-based survey on movie language orientation, movie exposure (from which exposure to tobacco portrayals was estimated), smoking-related expectancies, and smoking susceptibility. Results: Path and mediation analyses indicated that English-language movie orientation was associated with greater movie smoking exposure, leading to more positive smoking-related expectancies and greater youth smoking susceptibility. Conclusion: Consistent with research on the influence of US culture on the smoking of Mexican-heritage youth in the United States, findings suggest that orientation toward English-language movies may put youth in Mexico at risk for smoking initiation. Findings extend existing research on intercultural contact and cigarette smoking with Hispanic youth in the United States to youth in Mexico. Implications for future research are discussed. Implications: This study is one of the first to investigate the influence of remote intercultural contact with US culture on Mexican youth's smoking-related expectancies and susceptibility. This study investigated pathways by which youth's movie language orientation (English vs. Spanish) exposed them to movie smoking through US- and Mexico-produced movies, thereby influencing their smoking-related cognitions. Findings provide initial empirical evidence of a significant association between US remote intercultural contact and smoking among youth in Mexico. An important next step is to investigate how this process unfolds longitudinally and to investigate additional ways youth may engage with US culture to affect their smoking behaviors.